Strategi Kreatif Humas dalam Menggugah Semangat Komunitas Mengembangkan Kampus Islam - Zainal Abidin (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2024)
The aim of this research is to analyze the role of public relations management in increasing community participation in developing STIT Jembrana, Bali. This research uses a qualitative case study type approach. The data collection uses interviews, observation and documentation. Research data sources consist of primary and secondary sources. Primary sources were obtained from interviews with supporting informants as well as observations in the form of direct observations to strengthen the data found from the interviews. Meanwhile, secondary data sources were obtained from documentation in the form of activity reports, pictures and photos related to public relations activities. This research also checked the validity of the data by triagulating sources, methods and theories. The data analysis technique uses data reduction, data presentation and drawing conclusions. The research results obtained are that public relations management at STIT Jembrana, Bali uses Terry's theory with POAC components, namely: Planning, carried out by analyzing the needs and desires of the community both internally and externally, Organizing (organizing) carried out by selecting and assigning the right resources in its field, Actuating (implementation) implements public relations through activities carried out according to the schedule in the academic calendar, and Controling (control/evaluation) is carried out by monitoring and evaluating the implementation of activity programs with predetermined initial planning. The form of community participation consists of labor/physical participation, thinking and financial participation.